2021
DOI: 10.1007/s12012-021-09704-8
|View full text |Cite
|
Sign up to set email alerts
|

Metoprolol Protects Against Arginine Vasopressin-Induced Cellular Senescence in H9C2 Cardiomyocytes by Regulating the Sirt1/p53/p21 Axis

Abstract: Cardiomyocyte senescence is involved in the pathological mechanism of cardiac diseases. Metoprolol is a β1 receptor blocker used for the treatment of hypertension. Recent studies show that Metoprolol can protect cardiomyocytes against ischemia injury. The present study aims to investigate the protective effects of Metoprolol against arginine vasopressin (AVP)-induced cellular senescence in cultured cardiomyocytes. The cell proliferation assay and cytotoxicity lactate dehydrogenase assay showed that the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…There is limited evidence to suggest that β-blockers affect visfatin levels in the human body. Treatment with metoprolol ameliorated decreased intracellular visfatin activity in cardiomyocytes [ 33 ], while Skoczylas et al observed significant reductions in plasma visfatin levels compared to baseline values after 6 weeks of treatment with bisoprolol in patients with essential hypertension [ 19 ]. Contrary to previous studies and our expectations, we found that β-blocker users had higher levels of visfatin.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited evidence to suggest that β-blockers affect visfatin levels in the human body. Treatment with metoprolol ameliorated decreased intracellular visfatin activity in cardiomyocytes [ 33 ], while Skoczylas et al observed significant reductions in plasma visfatin levels compared to baseline values after 6 weeks of treatment with bisoprolol in patients with essential hypertension [ 19 ]. Contrary to previous studies and our expectations, we found that β-blocker users had higher levels of visfatin.…”
Section: Discussionmentioning
confidence: 99%
“…Because decreased cardiac -AR reactivity leads to decreased cardiac function and muscle strength reserve, treatments to restore -AR reactivity (such as beta blockers) can improve cardiac function in older patients [ 79 ]. To reduce sympathetic nerve activity, studies have found that metoprolol can down-regulate arginine vasopressin (AVP) induced acetylated p53 and p21 expression, so metoprolol can protect AVP induced cardiomyocyte senescence [ 80 ].…”
Section: Changes In Metabolism Of Hormones During Cardiac Agingmentioning
confidence: 99%
“…It's really a hot topic in life science and biomedicine. Here are summarized tables on major studies of axis and eCVD or fCVD in cardiovascular journals (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and non-cardiovascular journals (25-42) (Table 1 & Table 2). However, exception of several reviews on "Brain-Gut-Bone Marrow Axis" (Santisteban MM, et al 2016) (43) and "Heart-Brain Axis" (Tahsili-Fahadan P & Geocadin RG, 2017) (44), which involved in cardiovascular risk, the mechanisms and treatment, most of these studies, and reviews or comments just only involved in targeting these "branch axis" of eCVD (atherosclerosis, hypertension, and others), for example, the CCL2-CCR2 axis (Georgakis MK, et al 2022;Crea F, 2022) (45,46).…”
Section: Current Major Studies On Axis and Cvdmentioning
confidence: 99%